Pembelajaran Berdiferensiasi Dalam Kurikulum Merdeka Belajar: Strategi Untuk Meningkatkan Hasil Belajar Siswa Dalam Pendidikan Agama Kristen - Elfin Warnius Waruwu; Dyulius Thomas Bilo (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2025)
Differentiated Learning in Merdeka Belajar Curriculum has become a major concern in an effort to improve student learning outcomes, especially in Christian Religious Education subjects. This article examines the strategies used in differentiated learning to achieve this goal. The research methodology involves a systematic library study approach, where information related to differentiated learning and Merdeka Belajar Curriculum is collected from various sources in the library. Analysis and synthesis of findings from various sources of information were conducted to identify strategies that are effective in improving student learning outcomes. The results highlight the importance of a differentiated approach in teaching Christian Religious Education, including the use of diverse learning methods and differentiation-based assessment. The implication of the findings is that differentiated learning can be key to creating a learning environment that is inclusive and responsive to students' individual needs. By effectively implementing differentiated learning strategies, it is expected that student learning outcomes in Christian Religious Education will improve, in accordance with the vision of Merdeka Belajar Curriculum to empower every student to reach their maximum potential.